2019
DOI: 10.11118/actaun201967061457
|View full text |Cite
|
Sign up to set email alerts
|

Level of Inbreeding in Norik of Muran Horse: Pedigree vs. Genomic Data

Abstract: The objective of this study was to analyse the level of pedigree and genomic inbreeding in a herd of the Norik of Muran horses. The pedigree file included 1374 animals (603 stallions and 771 mares), while the reference population consisted of animals that were genotyped by using 70k SNP platform (n = 25). The trend of pedigree inbreeding was expressed as the probability that an animal has two identical alleles by descent according to classical formulas. The trend of genomic inbreeding was derived from the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previous studies [ 33 ], reported that the ROH segments of 2–4 Mb represent the inbreeding of distant generations of the ancestors (13–25 generations ago), which cannot usually be captured using pedigree information. The ROH segments > 8 Mb represent the proportion of autozygosity originated from ancestors that were born 6–7 generations ago and the ROH longer than 16 Mb reflect ancestors that were born 3–6 generations ago [ 34 ]. This was also visible in our data in which the correlation coefficient between F PED and F ROH tended to increase along with the increase of the number of generations registered in pedigree data.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 33 ], reported that the ROH segments of 2–4 Mb represent the inbreeding of distant generations of the ancestors (13–25 generations ago), which cannot usually be captured using pedigree information. The ROH segments > 8 Mb represent the proportion of autozygosity originated from ancestors that were born 6–7 generations ago and the ROH longer than 16 Mb reflect ancestors that were born 3–6 generations ago [ 34 ]. This was also visible in our data in which the correlation coefficient between F PED and F ROH tended to increase along with the increase of the number of generations registered in pedigree data.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic coefficients derived from animals/populations can be calculated without pedigree records or incomplete pedigree information. The inbreeding coefficients of many horse breeds—including Arabian (Al Abri, König von Borstel, Strecker, & Brooks, 2017), Lipizzan (Grilz‐Seger et al., 2019), Thoroughbred (Fawcett et al., 2019), Saxon‐Thuringian (Metzger et al., 2015) and Norik of Muran (Kasarda et al., 2019)—have been studied in a genomic‐wide view.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies in livestock species have focused on the estimation of genetic diversity using both pedigree data and molecular information: in cattle [4,5], pigs [6], and horses. In horses, genetic diversity was estimated using pedigree data and microsatellites (e.g., in thoroughbred horses [7], Franches-Montagnes [8], and Belgian Draught horse [9]) and, more recently, using pedigree and high-density SNP information (Norik of Muran horses [10]).…”
Section: Introductionmentioning
confidence: 99%